Minerals and resistant starch in red banana flours ‘São Domingos’ triploid (AAA) (Research, Society and Development, 2021)
Banana is one of the main agricultural crops in the world, of great socioeconomic importance for developing countries and with important characteristics for the manufacture of flour. Among the varieties of bananas, there are those with red peels, which stand out for their high levels of bioactive compounds, such as precursors of vitamin A. However, there are still gaps in knowledge regarding resistant starch and minerals present in these varieties. Thus, the study aimed to characterize the levels of minerals and resistant starch present in the flour of the peel and pulp of the red banana ‘São Domingos’ (AAA). The flours, peel and pulp, were produced from fruits obtained in a rural property, sanitized, sliced, peeled, dried in an oven with forced air circulation at 55 ºC and ground in a roller-knife mill. Thus, they were subjected to the analysis of moisture, ash, minerals (potassium, phosphorus, calcium, magnesium, sulfur, copper, manganese, zinc, iron and sodium) and resistant starch. Flours did not differ in moisture content. The bark flour showed higher levels of ash, potassium, magnesium, phosphorus, zinc and sodium. Potassium and manganese were the, macro and micromineral, present in greater quantities in both flours. Both flours showed moisture within the limit established by the legislation. Shell flour has a higher mineral content; while pulp flour has almost twice as much resistant starch. The 'São Domingos' red-skinned banana flours have characteristics similar to those of other AAA triploids.